Atypical regulators of Wnt/β-catenin signaling as potential therapeutic targets in Hepatocellular Carcinoma. Issue 11 (June 2017) - Chen, Jianxiang; Rajasekaran, Muthukumar; Hui, Kam M
Hepatocellular carcinoma is one of the most common causes of cancer-related death worldwide. Hepatocellular carcinoma development depends on the inhibition and activation of multiple vital pathways, including the Wnt signaling pathway. The Wnt/β-catenin pathway lies at the center of various signaling pathways that regulate embryonic development, tissue homeostasis and cancers. Activation of the Wnt/β-catenin pathway has been observed frequently in hepatocellular carcinoma. However, activating mutations in β-catenin, Axin and Adenomatous Polyposis Coli only contribute to a portion of the Wnt signaling hyper-activation observed in hepatocellular carcinoma. Therefore, besides mutations in the canonical Wnt components, there must be additional atypical regulation or regulators during Wnt signaling activation that promote liver carcinogenesis. In this mini-review, we have tried to summarize some of these well-established factors and to highlight some recently identified novel factors in the Wnt/β-catenin signaling pathway in hepatocellular carcinoma. Impact statement: Early recurrence of human hepatocellular carcinoma (HCC) is a frequent cause of poor survival after potentially curative liver resection. Among the deregulated signaling cascades in HCC, evidence indicates that alterations in the Wnt/β-catenin signaling pathway play key roles in hepatocarcinogenesis. In this review, we summarize the potential molecular mechanisms how the microtubule-associated Protein regulator of cytokinesis 1 (PRC1), a direct Wnt signaling target previously identified in our laboratory to be up-regulated in HCC, in promoting cancer proliferation, stemness, metastasis and tumorigenesis through a complex regulatory circuitry of Wnt3a activities.